The Effect of Zumba Exercise to Women's Waist Hip Ratio - Laksmi Indreswari; Yunita Dewi Anggraeni; Rena Normasari (Journal of Agromedicine and Medical Sciences, 2020)
Abdominal obesity is a global public health problem. The high prevalence of abdominal obesity triggers an increase in morbidity and mortality in chronic diseases such as diabetes mellitus, cardiovascular, and cancer. One of the causes of the high prevalence of abdominal obesity is the lack of physical activity. Prevention efforts are needed through the identification of risk factors such as measurement of waist hip ratios. The respondents of this study were divided into two groups: 28 respondents who did zumba exercise for four weeks and 28 control respondents. The statistical test performed was a paired t-test comparison test. The results of this study indicate the value of t-count > t-table value (7.184 > 2.052) and the significance of 0.000 < 0.05. These results indicate that there is a decrease in the waist hip ratio after doing zumba exercise for four weeks.